SISTEM USAHATANI TANAMAN DAN TERNAK SAPI DI LAHAN KERING KALIMANTAN SELATAN (STUDI KASUS DI DESA BANUA TENGAH DAN SUMBER MAKMUR, KECAMATAN TAKISUNG KABUPATEN TANAH LAUT) - Eni Siti Rohaeni (Universitas Sebelas Maret, 2015)
Farming is done in general farmers polyculture with the aim to increase revenues and avoid crop failure. Farming is carried out consisting of several commodities both crops and livestock. Generally farming is done is still not provide sufficient revenues Living Needs. This study aims to determine the system of crop and cattle farming in upland South Kalimantan, and to determine whether the income generated from farming to meet to the needs of decent living. This research is a case study in the village of Central Banua and Sumber Makmur, Takisung district, Tanah Laut regency. This study was conducted in 2012. Research was conducted by way of a survey approach Focus Group Discussion conducted with the involvement of several community leaders /key figures to describe the profile , potential and problems in the region or village level. The analysis used is analysis of revenue, contribution revenue, and contribution to the farm income Living Needs (KHL). The results showed that the dominant farming by farmers in the study site, namely rice, sweet corn and cattle. Mean scale paddy cultivation to 0.62 ha, 0.68 ha of sweet corn and cattle 5.15 Animal Unit. Farming is done generating the value of R/C is more than one viable means for cultivated. The revenue contribution of rice 24.52 %, 50.83 % sweet corn and cows 24.65 % . Contribution income from rice farming, sweet corn and beef cattle on Living Needs of 50.94 %.